PERENCANAAN PERSEDIAAN OBAT DENGAN METODE ECONOMIC ORDER QUANTITY(STUDI KASUS DI APOTEK â€œXâ€, â€œYâ€, â€œZâ€ DI KOTA SURABAYA) - WAHYU NUGROHO, ROBI (Jurnal Akuntansi AKUNESA, 2018)
Inventory one of the most important components in the trading business especially pharmacies. So there is a need for inventory planning so that the operational activities of the pharmacy is running well. But at this time the pharmacy has not applied any method in inventory planning is limited to estimates only. So the purpose of this study is to know the planning process of three pharmacies when reviewed by the method Economic Order Quantity. So it can be known when the optimal order, how frequent purchases in a year, how much security, and the time of repurchase of inventory, maximum inventory, and total cost of medical supplies. The results of this study indicate that there are total cost savings from pharmacies